Evasão discente no ensino superior: estudo de caso no Instituto Federal de Educação, Ciência e Tecnologia do Ceará (Campus Sobral) - Amaral, João Batista do (2013)
The university, in face of economic, political and cultural recent changes that influence education, is invited to rethink and transform its ties with society. Several factors need to be corrected and others, eliminated, so that students can have not only access to the university, but also a guarantee of graduation. This study aimed at identifying and analyzing the causes of students’ dropout from higher education at Federal Institute of Education, Science and Technology of Ceará State, Sobral Campus, in the point of view of the dropped out students, during the years of 2010 and 2011, intending to propose actions to minimize this phenomenon. To conduct this work, the case study was chosen as a method along with field, documental and literature researches. A questionnaire was sent by email to 140 dropout students from the five undergraduate courses of the institution, which formed the target population of the survey. However, only 35 answered it, and those constituted the simple random sample analyzed in this study. The research showed six internals and externals factors that motivated the evasion. As internal factors, it indicated the compatibility of the course with the need to work, the socioeconomic conditions faced by the students, the discovering of new interests related to the option for a new course, and the dissatisfaction with the course, that undermines the students’ achievement in the disciplines. In the external dimension, the survey revealed a lack of institutional actions to prevent evasion of students, as well as the difficulty of access to the benefits of the Student Assistance Program. The results led to the understanding that the evasion in the undergraduate courses at Federal Institute of Education, Science and Technology of the Ceará State, Sobral Campus, is not a process that depends only on the student, but it is also an institutional phenomenon, reflecting the absence of a strategy to keep students in the course of their choice. It was noticed that several factors that can influence or determine the dropout of students in a Higher Education Institution, as psychological, social, economic, educational, political and administrative ones, among others.